Gledališka produkcija in distribucija v različnih evropskih mestih - Toome, Hedi-Liis (Amfiteater (Ljubljana), 2015)
The aim of the article is to compare the production and distribution of theatre in the cities of Aarhus (Denmark), Debrecen (Hungary), Groningen (The Netherlands), Maribor (Slovenia) and Tartu (Estonia), and to discern whether the differences or similarities in theatre systems can be related to the differences and similarities in production (productions), distribution (performances) and consumption (visits). The findings are based on the analysis of the extensive data recorded by the City Study of the Project on European Theatre Systems (STEP). All the public theatrical events of one season (between the years 2010~2011) of these five cities were collected and divided into seven types of theatre: Spoken Theatre, Dance, Musical Theatre, Kleinkunst, Puppet and Object Theatre, Cirque Nouveau and Show, and Physical Theatre. Spoken Theatre clearly dominates in the majority of the cities (competing often with Musical Theatre). In the article, we also discuss how the cultural traditions, the structure of the theatre system, the policy aspects of the theatre system and the economics of theatre production influence the production, distribution and consumption of theatre.
Keywords: distribucija gledališča; distribution of theatre; Europe; Evropa; genres; gledališče; gledališka produkcija; gledališki sistemi; gledališki tipi; international comparative theatre survey; mednarodne primerjave; ponudba; production of theatre; STEP; supply; theater; theatre systems; theatre types; žanri